Systemic vasculitis associated with vemurafenib treatment: Case report and literature review. Issue 46 (November 2016) - Mirouse, Adrien; Savey, Léa; Domont, Fanny; Comarmond, Cloé; Barete, Stéphane; Plaisier, Emmanuelle; Rouvier, Philippe; Cacoub, Patrice; Saadoun, David
Abstract: Rationale: Vemurafenib, an inhibitor of mutated B-rapidly accelerated fibrosarcoma, is frequently used in the treatment of melanoma and Erdheim–Chester disease (ECD) patients. Inflammatory adverse effects have been increasingly reported after vemurafenib treatment. Patient concerns and diagnose: We report 6 cases of vemurafenib-associated vasculitis, of whom a personal case of a 75-year-old man with history of ECD who developed purpura and rapidly progressive pauci-immune glomerulonephritis during treatment with vemurafenib. Intervention: In the 5 others cases from the literature, all patients presented skin vasculitis, and with joint involvement in 60% of them. Vemurafenib treatment was stopped (n = 3), continued at reduced doses (n = 1), or continued at the same dose (n = 2). Outcomes: Three patients (50%) received corticosteroids combined with cyclophosphamide (n = 1), and all achieved remission of vasculitis. One patient experienced vasculitis relapse after vemurafenib therapy was restarted. Lessons: Systemic vasculitis is a rare vemurafenib-associated adverse event that may be life-threatening.